Hyperthermia-driven aberrations of secreted microRNAs in breast cancer in vitro. (17th August 2016) - Erbes, Thalia; Hirschfeld, Marc; Waldeck, Silvia; Rücker, Gerta; Jäger, Markus; Willmann, Lucas; Kammerer, Bernd; Mayer, Sebastian; Gitsch, Gerald; Stickeler, Elmar
Abstract: Purpose: Expression profile alterations of nine breast cancer (BC)-associated secreted microRNAs (miRs) were determined under microenvironmental alterations occurring in tumour progression, metastasis or specific oncological treatment modalities. Thereto, the potential influence of the exogenic stimuli hypoxia, acidosis and hyperthermia was investigated in vitro . Material and methods: Four established BC cell lines were applied as in vitro BC model systems. Quantitative analyses of secreted microRNA specimens were performed by RNA isolation from cell culture supernatant and subsequent real-time PCR in cells under physiological versus hypoxic, acidic or hyperthermia conditions. Results: The in vitro application of exogenic stimuli hypoxia, extracellular acidosis and hyperthermia caused heterogeneous expression alterations for the investigated secreted miRNA phenotypes. The majority of relevant exogenic stimuli-dependent microRNA expression alterations were restricted to single events displaying distinct cell type and stimulus dependent correlations only. Most remarkably, hyperthermia triggered a uniform significant down-regulatory effect on the expression levels of the three secreted microRNAs miR-10b, miR-15b and miR-139, respectively. The marked decrease in miR-10b and miR-15b levels was detectable in all four, while miR-139 was found significantly reduced in three out of four BC cell lines. Conclusion: Hyperthermia-dependent down-regulatory influence on three distinct BC-related microRNAs in vitro generates translational aspects for clinical BC treatment, since the identified microRNAs miR-10b, miR-15b and miR-139 are known to have oncogenic as well as tumour suppressor functions in BC. However, an evaluation regarding the potential impact of microRNA-related hyperthermia-dependent alterations for innovative BC treatment approaches demands further analysis including in vivo data.